Participatory and transdisciplinary studies of Brucella infection in humans and animals in Yunnan Province, China—Lessons learned - Wengui Li; Xiangdong Yang; Lindahl, Johanna F.; Guorong Yang; Gilbert, Jeffrey; Unger, Fred (MDPI, 2021)
Brucellosis is an important zoonosis occurring globally. In addition to the risk for disease in humans, the disease causes production losses, since the disease in livestock is characterized by abortion and other reproductive failures. The disease is a public health concern in China, but no information is available on knowledge, perception and awareness of potential risk groups such as farmers, butchers and animal health workers; yet successful control requires compliance of those affected groups to be effective. Following the principles of the Ecohealth approach, emphasis was given to participation of all relevant stakeholders, use of qualitative and quantitative tools, and cross-sectorial collaboration. Data collection included on-farm questionnaires (N = 192) and collection of bulk milk samples of goat (N = 40), cattle (N = 45) and buffalo (N = 41) from farms, as well as serum samples (N = 228) from humans. Milk samples were tested with an ELISA for presence of antibodies, while a serum agglutination test was used for human samples. Qualitative work included 17 focus group discussion (FGD) with villagers and 47 in-depth interviews (IDI) with village animal health workers, doctors, and butchers, focused on knowledge, perception and awareness on zoonoses including brucellosis. Results from questionnaires indicate that abortions are a common problem; cattle with abortion history are kept for further insemination and the milk still consumed or sold. Antibodies against Brucella were detected in cows’ (5/45) and goats’ (1/40) milk samples, and in human samples (5/126) in Yiliang, while in Mangshi, all buffalo (N = 41) and humans (N = 102) were negative. FGD and IDI results showed an alarmingly low knowledge and awareness on zoonoses; particularly, low awareness about brucellosis was noted, even among the professional groups. Collaboration between village animal health workers and doctors was uncommon. No confirmed brucellosis cases were found in retrospective investigation of hospital and veterinary stations. This study demonstrates the presence of brucellosis in livestock and humans in Yunnan, indicating a non-negligible risk for humans. It is also made apparent that there is a need for increased awareness among both farmers and professionals in order to reduce the risk of zoonotic transmissions.